2021
DOI: 10.21203/rs.3.rs-960579/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Androgenic TRPM8 activity drives sexual dimorphism in a murine model of chronic migraine

Abstract: The mechanisms contributing to the high prevalence of chronic migraine in females are yet elusive. Here, we used a mouse model of nitroglycerin-induced chronic migraine that displays a sexual dimorphic phenotype and unveiled a role of TRPM8 as a testosterone receptor that provides antinociceptive resilience exclusively in males. Nitroglycerin induced similar mechanosensitivity to both sexes trough activation of TRPA1 channels, but triggered persistent hypersensitivity solely in females, as males readily recove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Some studies have shown a sexual dimorphism in migraine-like models, with female rodents showing higher nociceptive and anxiety-like responses ( Araya et al, 2020 ). Recently, using a migraine model induced by nitroglycerin i. p. injection, a sexual dimorphic effect was detected, in which females had higher nociception than males ( Alarcón-Alarc ón et al, 2021 ). However, most of the studies using models of migraine have not evaluated sexual differences, and male mice or rats are normally tested ( Khasar et al, 2009 ; Taheri et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a sexual dimorphism in migraine-like models, with female rodents showing higher nociceptive and anxiety-like responses ( Araya et al, 2020 ). Recently, using a migraine model induced by nitroglycerin i. p. injection, a sexual dimorphic effect was detected, in which females had higher nociception than males ( Alarcón-Alarc ón et al, 2021 ). However, most of the studies using models of migraine have not evaluated sexual differences, and male mice or rats are normally tested ( Khasar et al, 2009 ; Taheri et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using the migraine model induced by nitroglycerin i.p. injection, a sexual dimorphic effect was detected in which females had higher nociception than males [2]. However, most of the studies using models of migraine did not evaluate the sexual differences, and male mice or rats are normally tested [32,50].…”
Section: Discussionmentioning
confidence: 99%
“…TRPM8 is expressed mainly in a subpopulation of primary afferent neurons present in dorsal root and trigeminal ganglia, and in the nodose and geniculate ganglia of the peripheral nervous system. In these neurons, TRPM8 participates in the amplification of pain sensation after injury [6], suggesting that TRPM8 channel blockers could be effective for the treatment of chronic pain and migraine [7,8]. Furthermore, TRPM8 modulators have been investigated as therapeutics for the symptomatology of bladder pain syndromes, given their increased expression in patients suffering from these disorders [9].…”
Section: Introductionmentioning
confidence: 99%